Financial performance of banks in Pakistan after Merger and Acquisition - Qamar Abbas; Ahmed Imran Hunjra; Rauf I. Azam; Muhammad Shahzad Ijaz; Maliha Zahid (Journal of Global Entrepreneurship Research, 2014)
Business transactions are going to be fast day by day because of dynamic changes in the global environment. Merger and Acquisition is a strategy adopted by the organizations globally to meet the needs of recent dynamic business environment. It has achieved much attention and importance in corporate world. In Pakistan, this strategy has been used widely in banking sector. Therefore, the objective of the study is to evaluate the financial performance of banks in Pakistan after M&A. The financial and accounting data for 10 banks was taken from the Financial Statement Analysis by State Bank of Pakistan. Profitability & Efficiency, Leverage, and Liquidity ratios were used to measure the financial performance, where pre and post ratio analysis was done. Results of the study show that there is no positive improvement in the financial performance of the banks in Pakistan after Merger and Acquisition.
Keywords: 650; Merger and Acquisition; Financial Performance; Profitability; Liquidity; Leverage; Pre & Post Analysis